P157 Cancer Patients With Severe Community Acquired Pneumonia Have Poorer Outcomes Due To Increased Illness Severity And Septic Shock At Admission To Intensive Care. (10th November 2014) - José, RJ; Mohammad, AO; Goldring, JP; Chambers, RC; Brown, JS; Agarwal, B
Abstract : Introduction: Patients with community acquired pneumonia (CAP) and an underlying diagnosis of cancer have worse outcomes. However, the characteristics of cancer patients with severe CAP admitted to intensive care units are not well defined. Methods: An observational study of patients admitted to a University hospital ICU with a primary diagnosis of CAP between January 2006 and October 2011. Results: 96 patients met our inclusion criteria for a diagnosis of severe CAP. 19 (19.8%) had cancer at the time of admission to ICU (57.9% with haematological malignancy and 42.1% with solid organ cancer). There were no statistically significant differences in age, gender or co-morbidities between those with and those without cancer. Patients with cancer had significantly higher median [IQR] APACHE II (25 [20–19] vs 20 [16–24]; p = 0.009), SAPS (51 [42–62] vs 42 [34–53]; p = 0.039) and SOFA (12 [10–13] vs 9 [4–12]; p = 0.018) scores and a longer median [IQR] time interval between hospital and ICU admission (2 [1–5] vs 1 [0–3] days; p = 0.049). There were no statistically significant differences in the proportion of patients receiving mechanical ventilation or renal support and no differences in the duration of mechanical ventilation or duration of ICU or hospital stay. Patients with cancer included a significantly greater proportion of patients receiving vasopressors (89.5% vs 63.6%, p = 0.030) and a markedly increased ICU (68.4% vs 31.2%, p = 0.004) and hospital mortality (78.9% vs 33.8%, p = 0.001). There were no significant differences in leukocyte counts, CRP, clotting (PT, APTT and INR), renal function (urea and creatinine) or liver function (AST and ALT). There were no significant differences in heart rate, temperature, systolic blood pressure or oxygenation index. However, patients with cancer had significantly lower median diastolic blood pressure (40 mmHg vs 50 mmHg, p = 0.026). Conclusion: Cancer patients with severe CAP continue to have an increased risk of death that appears to be related to increased illness severity at the time of ICU admission associated with septic shock. A delay in recognising the need for intensive care support in cancer patients with severe CAP may possibly explain the increased illness severity at the time of ICU admission.